On the Sizes of Maximal Independent Sets of Cylindrical Grid Graphs - Barbosa, Rommel Melgaço; Cappelle, Márcia Rodrigues (Trends in Computational and Applied Mathematics, 2016)
If a graph G has exactly t different sizes of maximal independent sets, G belongs to a collection called Mt. For the Cartesian product of the graph Pn, the path of length n, and Cm, the cycle of length m, called cylindrical grid, we present a method to find maximal independent sets having different sizes and a lower bound on t, such that these graphs belong to Mt.